The Role of the School Principal in Strengthening Students’ Personal Development Through the Optimization of Guidance and Counseling Services: A Literature Review - Lisa Anggraini; Neviyarni N; Yarmis Syukur (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article reviews various literature findings regarding the leadership role of school principals in strengthening Guidance and Counseling (BK) services oriented toward student personal development. The study focuses on three domains: the regulations that underlie the implementation of BK services, the implementation of the principal's role in daily school activities, and the challenges that frequently arise in implementing these services. Furthermore, this article offers problem-solving strategies based on the needs of today's educational institutions. Overall, the literature indicates that the success of BK services is influenced by the quality of the principal's policies, the availability of supporting facilities, and a collaborative culture among all school members.